Representation of Cross-Cultural Relations in the Bali Agung Theater at Taman Safari & Marine Park Bali : A Discourse in Balinese Tourism Performing Arts - Gede, Yoga Kharisma Pradana; Surya Wijaya, Nyoman; Ketut Purnaya, I Gusti (Institut Seni Indonesia Denpasar, 2024)
This article aims to understand and explain the discourse on cross-cultural relations in the Bali Agung Theater at Taman Safari & Marine Park Bali. The Bali Agung Theater at Taman Safari & Marine Park Bali is an innovative Balinese performance art for tourism purposes at Taman Safari & Marine Park Bali. As a Balinese tourism performing art, there is a representation of cross-cultural relations in performance scenes featuring typical Chinese arts. The narrative discourse of the Bali Agung Theater was developed by actors based on the folklore of traditional Balinese society. The main problems: 1) What are the forms of cross-cultural relations in the Bali Agung Theater at Taman Safari & Marine Park Bali?; 2) What is the discourse on cross-cultural relations in the Bali Agung Theater at Taman Safari & Marine Park Bali?. The cross-cultural discourse analysis in the Bali Agung Theater at Taman Safari and Marine Park Bali was completed using qualitative methods. Primary data was collected through observations at the Taman Safari and interviews with actors at the Bali Agung Theater. Data achievements are complemented by secondary data collection from literature studies. All data were analyzed using knowledge-power relations theory and structuration theory. The research results show that: 1) Taman Safari & Marine Park Bali displays discourse on cross-cultural relations through Balinese cultural acculturation at the Bali Agung Theatre. Cultural acculturation can be seen in art in the form of props and dance movements; 2) The discourse on cross-cultural relations in the Bali Agung Theater consists of cultural heritage discourse, educational discourse, and violence discourse. This theatrical discourse centers on Kang Ching Wei, King, and Dewi Danu.